2443. Searching for the Optimal Treatment Regimen for Metallo-β-Lactamase Producing Enterobacteriaceae: Aztreonam Plus Ceftazidime–Avibactam vs. Aztreonam Plus Meropenem–Vaborbactam. (26th November 2018) - Biagi, Mark; Wenzler, Eric
Abstract: Background: Pathogens harboring metallo-β-lactamase (MBL) enzymes pose a large threat to public health. Aztreonam (ATM) is not hydrolyzed by MBLs but is inactivated by other β-lactamases, which are often co-harbored in MBL-producers. Ceftazidime/avibactam (CAZ/AVI) and meropenem/vaborbactam (MER/VBR) are novel β-lactam/β-lactamase inhibitors (BL/BLI) with potent activity against serine β-lactamase producing Enterobacteriaceae . Combining ATM with BL/BLI agents may provide activity against Enterobacteriaceae producing serine and MBLs. Methods: Two clinical E. coli isolates were used. MICs were determined in triplicate and modal values are reported. Time kill analyses were performed in triplicate at standard inoculum (10 6 ). Each agent was tested alone and in combination at either f Cmax or ¼, ½, 1, 2, or 4× MIC based on susceptibility. Bactericidal activity was ≥3 log10 reduction in CFU/mL from the starting inoculum. Synergy was ≥2 log10 reduction in CFU/mL compared with the most active agent alone. Antagonism was ≥2 log10 increase in CFU/mL compared with the most active agent alone. Results: Genotypic/phenotypic susceptibilities are in Table 1. Against EC-1, ATM alone at f Cmax had no activity. When combined with CAZ/AVI or MER/VBR, respectively, synergy was observed with average log10 decrease in CFU/mL at 24 hours of 3.92 and 5.04 (Figure 1a). Synergy seemed to be driven solely by the addition of the BLI as ATM/CAZ and ATM/MER did not demonstrate synergy (Figure 1a). Against EC-2, ATM alone at 1/4× MIC showed no activity (Figure 1b). Combining ATM with either CAZ/AVI or MER/VBR did not improve the activity or demonstrate synergy (Figure 1b). Interestingly, removing CAZ significantly improved the activity of ATM/AVI. Conclusion: There were no significant differences in activity or synergy observed between the combinations of ATM with either CAZ/AVI or MER/VBR against serine- and MBL-producing E. coli . Synergy appears to be driven by the ATM-BLI combinations, with ATM-AVI demonstrating more consistent synergy than ATM-VBR. Further studies including more isolates and combinations are warranted. Disclosures: E. Wenzler, Melinta Therapeutics: Speaker's Bureau, Speaker honorarium.